The Future Life of Trauma : Partitions, Borders, Repetition - Yusin, Jennifer (Book collections on Project MUSE., 2017)
"The Future Life of Trauma elaborates a transformation in the concepts of trauma and event by situating a groundbreaking encounter between psychoanalytic and postcolonial discourse. Proceeding from the formation of psychical life as presented in the Freudian metapsychology, it thinks anew the relation between temporality and traumatized subjectivity, demonstrating how the psychic event, as a traumatic event, is a material reality that alters the character of the structure of repetition. By examining the role of borders in the history of the 1947 partition of British India and the politics of memorialization in postgenocide Rwanda, The Future Life of Trauma brings to light the implications of trauma as a material event in contemporary nation-formation, sovereignty, and geopolitical violence. In showing how the form of the psyche changes in the encounter, it presents a challenge to the category of difference in the condition of identity, resulting in the formation of a concept of life that elaborates a new relation to destruction and finitude by asserting its power to transform itself."--